2012
DOI: 10.1093/infdis/jis446
|View full text |Cite
|
Sign up to set email alerts
|

In Enterovirus 71 Encephalitis With Cardio-Respiratory Compromise, Elevated Interleukin 1 , Interleukin 1 Receptor Antagonist, and Granulocyte Colony-Stimulating Factor Levels Are Markers of Poor Prognosis

Abstract: Given that IL-1β has a negative inotropic action on the heart, and that both its natural antagonist, IL-1Ra, and G-CSF are being assessed as treatments for acute cardiac impairment, the findings suggest we have identified functional markers of EV71-related cardiac dysfunction and potential treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 50 publications
5
63
1
1
Order By: Relevance
“…IL-1β, IL-1Rα, and G-CSF were recently reported by Griffiths et al as prognostic markers for EV71-infected hospitalized Malaysian children [18]. They tested IL-8 as well but did not find any significant changes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…IL-1β, IL-1Rα, and G-CSF were recently reported by Griffiths et al as prognostic markers for EV71-infected hospitalized Malaysian children [18]. They tested IL-8 as well but did not find any significant changes.…”
Section: Discussionmentioning
confidence: 84%
“…It has been proven that massive proinflammatory cytokines play critical roles in the pathogenicity of EV71 infection [13][14][15][16]. It has been reported that interleukin-1β (IL-1β), IL-1Rα, IL-6, IL-10, IL-13, interferon gamma (IFN), granulocyte colony-stimulating factor (G-CSF), and tumor necrosis factor alpha (TNFα) in serum and cerebral spinal fluid (CSF) were elevated significantly in EV71-infected patients [14,[16][17][18]. Administration of intravenous immunoglobulin (IVIG), an important treatment for patients with BE and EV71-infected patients that contains natural antibodies against cytokines, was found to reduce levels of IL-6 and IL-8 at early stages of EV71 infection, and to possibly prevent disease progression to PE [19].…”
Section: Introductionmentioning
confidence: 99%
“…Scheld and colleagues showed elevated IL-1ra levels in the meningoencephalitis group [14]. Griffiths and colleagues also demonstrated that IL-1ra levels were lower in HFMD with viral encephalitis (enterovirus) as compared with HFMD without encephalitis [11]. Later data indicated that IL-1ra might have the beneficial effect of decreasing the severity of disease associated with overexpression of IL-1β [11].…”
Section: Resultsmentioning
confidence: 99%
“…Interleukin-1 (IL-1) is a proinflammatory cytokine that has been studied and reflects inflammation of the central nervous system [9,11]. A previous study showed that increased levels of interleukin 1 beta (IL-1β) and interleukin-1 receptor antagonist (IL-1ra) were associ-ated with seizure and febrile conditions [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation